1996
DOI: 10.1074/jbc.271.25.14897
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Binding of Serum Amyloid P to Type IV Collagen

Abstract: Serum amyloid P (SAP)1 is a 10-subunit (two flat pentameric discs stacked face to face) M r Ϸ 230,000 glycoprotein coded by a single gene on human and mouse chromosome 1 (1, 2). It is a member of the evolutionarily conserved pentraxin family (1). These are proteins that are made up of five identical noncovalently bound subunits arranged in a flat pentameric disc (1, 3). In vitro SAP binds to proteoglycans and fibronectin in a specific Ca 2ϩ -dependent manner (4 -6). Furthermore, SAP binds to the collagen-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…In peripheral tissues, SAP is associated with several ECM proteins, such as elastin in the skin and collagen and laminin in the glomerular basement membrane of the kidney (43)(44)(45)(46)(47)(48). The observation that fibrocytes are evident in experimental wound chambers within days of induction suggests that fibrocytes differentiate quickly after wounding (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral tissues, SAP is associated with several ECM proteins, such as elastin in the skin and collagen and laminin in the glomerular basement membrane of the kidney (43)(44)(45)(46)(47)(48). The observation that fibrocytes are evident in experimental wound chambers within days of induction suggests that fibrocytes differentiate quickly after wounding (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…All four are secreted glycoproteins widely distributed in most physiological fluids, including plasma and CSF (Barrett 1981;Baltz et al, 1982;Bowman and Kurosky 1982;. Moreover, all bind to a broad range of ligands (Barrett 1981;Capiau et al, 1986;Katnik et al, 1987;Aruga et al, 1993;Katnik et al, 1993;Zahedi 1996;Ashton et al, 1997;Langlois et al, 1997;Zahedi 1997;Kurdowska et al, 2000;Wilson and Easterbrook-Smith 2000;Kimura et al, 2001;Sen and Heegaard 2002) and have been found associated with clinical amyloid deposits in vivo (Table (1)) (Powers et al, 1981;Baltz et al, 1982;Van Gool et al, 1993;McHattie and Edington 1999;Calero et al, 2000). In addition all have been shown to mediate receptormediated endocytosis of ligands (see below).…”
Section: Extracellular Chaperonesmentioning
confidence: 99%
“…Serum amyloid P (SAP: a member of the pentraxin family) is known to bind to a diverse array of ligands (154)(155)(156), however, no clear biological function for this protein has yet been established. It has been reported that SAP has ATP-independent refolding chaperone activity, however, this was achieved using a very high molar excess of SAP and even then the recovery of heat-denatured lactate dehydrogenase activity was only 25% (157).…”
Section: Other Ecsmentioning
confidence: 99%